2006
DOI: 10.2135/cropsci2004.0757
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci underlying Resistance to Three Soybean Cyst Nematode Populations in Soybean PI 404198A

Abstract: Soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is a major pest of soybean [Glycine max (L.) Merr.] in the USA. Soybean plant introduction (PI) 404198A is one of the newly identified sources that can provide a broad spectrum of resistance to SCN. The objective of this study was to identify quantitative trait loci (QTL) associated with resistance to SCN races 1, 2, and 5 in PI 404198A. Linkage groups (LGs) G and A2 were found to be associated with resistance to race 1. QTL on LG G was located on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
68
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 41 publications
8
68
0
1
Order By: Relevance
“…rhg1 was identified by classical genetic analysis as a recessive gene (Caldwell et al 1960;Arelli et al 1992) which seems to be common to major SCN resistance sources and provides the major portion of resistance to race 3 and race 14 (Concibido et al 2004). Major quantitative trait loci (QTL) for resistance have been mapped across many resistance sources, including Peking and PI437654, PI90767, PI88788, PI209332, PI89772, and PI404198A (Concibido et al 1994(Concibido et al , 1996(Concibido et al , 1997(Concibido et al , 2004Webb et al 1995;Chang et al 1997;Heer et al 1998;Prabhu et al 1999;Meksem et al 2001a;Yue et al 2001;Guo et al 2006a), producing several loci and interactions among them (Huang et al 1997;Meksem et al 2001a;Concibido et al 2004). The QTL conferring the greatest level of resistance mapped to a genomic region containing rhg1 in linkage group (LG) G (Concibido et al 2004;Guo et al 2006a), and QTL clusters on each end of LG G were confirmed by meta-analysis, a statistical method for assessing whether QTLs detected on a linkage group map in different studies are located on the same locus or linked (Goffinet and Gerber 2000;Guo et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…rhg1 was identified by classical genetic analysis as a recessive gene (Caldwell et al 1960;Arelli et al 1992) which seems to be common to major SCN resistance sources and provides the major portion of resistance to race 3 and race 14 (Concibido et al 2004). Major quantitative trait loci (QTL) for resistance have been mapped across many resistance sources, including Peking and PI437654, PI90767, PI88788, PI209332, PI89772, and PI404198A (Concibido et al 1994(Concibido et al , 1996(Concibido et al , 1997(Concibido et al , 2004Webb et al 1995;Chang et al 1997;Heer et al 1998;Prabhu et al 1999;Meksem et al 2001a;Yue et al 2001;Guo et al 2006a), producing several loci and interactions among them (Huang et al 1997;Meksem et al 2001a;Concibido et al 2004). The QTL conferring the greatest level of resistance mapped to a genomic region containing rhg1 in linkage group (LG) G (Concibido et al 2004;Guo et al 2006a), and QTL clusters on each end of LG G were confirmed by meta-analysis, a statistical method for assessing whether QTLs detected on a linkage group map in different studies are located on the same locus or linked (Goffinet and Gerber 2000;Guo et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Major quantitative trait loci (QTL) for resistance have been mapped across many resistance sources, including Peking and PI437654, PI90767, PI88788, PI209332, PI89772, and PI404198A (Concibido et al 1994(Concibido et al , 1996(Concibido et al , 1997(Concibido et al , 2004Webb et al 1995;Chang et al 1997;Heer et al 1998;Prabhu et al 1999;Meksem et al 2001a;Yue et al 2001;Guo et al 2006a), producing several loci and interactions among them (Huang et al 1997;Meksem et al 2001a;Concibido et al 2004). The QTL conferring the greatest level of resistance mapped to a genomic region containing rhg1 in linkage group (LG) G (Concibido et al 2004;Guo et al 2006a), and QTL clusters on each end of LG G were confirmed by meta-analysis, a statistical method for assessing whether QTLs detected on a linkage group map in different studies are located on the same locus or linked (Goffinet and Gerber 2000;Guo et al 2006b). To date, 12 molecular markers, including seven RFLP (restriction fragment length polymorphism), one RAPD (random amplified polymorphic DNA), one AFLP (amplified fragment length polymorphism) and two SSR (simple sequence repeat) linked to the rhg1 locus and to the QTL underlying resistance have been reported (Concibido et al 2004;Guo et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of the sources of resistance studied, the resistance gene rhg1 was mapped as a QTL onto chromosome 18 (formerly linkage group [LG] G). This gene was mapped in the SCN resistance sources PI 437654 (Webb et al, 1995), PI 209332 (Concibido et al, 1996), Peking, PI 90763, PI 88788 (Concibido et al, 1997;Glover et al, 2004), PI 89772 (Yue et al, 2001), PI 88287 (Bassuner et al, 2001), and PI 404198A (Guo et al, 2006). In addition, research showed that PI 437654 and PI 88788 have different alleles at rhg1 (Brucker et al, 2005).…”
mentioning
confidence: 99%
“…The rhg1 gene (GenBank accession No. AF506516) is located on linkage group (LG) G [chromosome 18 (Chr 18)] (Concibido et al, 1994;Webb et al, 1995;Chang et al, 1997;Concibido et al, 1997;Yue et al, 2001;Guo et al, 2006;Jiao et al, 2015). Although Melito et al (2010) reported no significant impact of the LRR-kinase gene on SCN resistance, nine rhg1 haplotypes and five protein allotypes were identified from 112 resistant plant introductions (PIs) and 34 derived cultivars, and all PIs-bearing Peking type alleles were resistant to race 3 (Ruben et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Rhg4 (GenBank accession No. AF506518) is located on LG A2 (Chromosome 8) (Concibido et al, 1994;Mahalingam and Skorupska, 1995;Webb et al, 1995;Chang et al, 1997;Heer et al, 1998;Guo et al, 2006). A total of 67 SNPs were identified in Rhg4 (Yuan et al, 2012) and five SNP markers were developed (Yuan, 2007).…”
Section: Introductionmentioning
confidence: 99%